2015
DOI: 10.1002/2015jg003044
|View full text |Cite
|
Sign up to set email alerts
|

Marsh‐atmosphere CO2 exchange in a New England salt marsh

Abstract: We studied marsh-atmosphere exchange of carbon dioxide in a high marsh dominated salt marsh during the months of May to October in 2012-2014. Tidal inundation at the site occurred only during biweekly spring tides, during which we observed a reduction in fluxes during day and night. We estimated net ecosystem exchange (NEE), gross primary production (GPP), and ecosystem respiration (R eco ) using a modified PLIRTLE model, which requires photosynthetically active radiation, temperature, and normalized differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 51 publications
8
63
2
Order By: Relevance
“…Tides also strongly influenced NEE at shorter timescales; while at the diel scale NEE was dominantly and largely synchronously linked to PAR as expected given the control of light on photosynthesis (Sturtevant et al, ), there was also a significant interaction between NEE and WTD, with nighttime flooding of the marsh during summer spring tides causing an instantaneous decrease in respiration (Figures b, c, and ). This is similar to the findings by Forbrich and Giblin (), Kathilankal et al (), and Moffett et al () who also observed a suppression of CO 2 fluxes during flooding tides. However, since flooding tides at Rush Ranch only occurred at night during growing season spring tides (Figure ), with receding water levels throughout the day (Figure b), we did not observe similar suppression of daytime NEE as reported by these other studies.…”
Section: Discussionsupporting
confidence: 92%
“…Tides also strongly influenced NEE at shorter timescales; while at the diel scale NEE was dominantly and largely synchronously linked to PAR as expected given the control of light on photosynthesis (Sturtevant et al, ), there was also a significant interaction between NEE and WTD, with nighttime flooding of the marsh during summer spring tides causing an instantaneous decrease in respiration (Figures b, c, and ). This is similar to the findings by Forbrich and Giblin (), Kathilankal et al (), and Moffett et al () who also observed a suppression of CO 2 fluxes during flooding tides. However, since flooding tides at Rush Ranch only occurred at night during growing season spring tides (Figure ), with receding water levels throughout the day (Figure b), we did not observe similar suppression of daytime NEE as reported by these other studies.…”
Section: Discussionsupporting
confidence: 92%
“…The net organic matter consumption inferred from the NCP/GPP ratios over the entire time-series is consistent with other findings in this and other salt marsh ponds that at least some ponds are sites of net organic matter consumption (Johnston et al 2003, Spivak et al submitted), as opposed to large sinks of atmospheric CO2 like the grass covered marsh platform (Forbrich and Giblin 2015). It has been hypothesized that one mechanism for pond expansion or collapse of marsh flanks into mudflats is the decomposition of the underlying or surrounding peat layers (Johnston et al 2003; in this system, net heterotrophy greatly exceeds photosynthesis over the study period and pond expansion via this mechanism seems likely.…”
Section: Metabolism Of the Study Pond In The Context Of Other Salt Masupporting
confidence: 77%
“…Site studies of these authors are dominated by marsh grass species which grow upright, either Spartina alterniflora (Kathilankal et al, 2008) or Spartina foliosa and Distichlis spicata (Forbrich and Giblin, 2015;Moffett et al, 2010). The water table threshold of 0.25 m reported in this study is similar to the value reported by Kathilankal et al (2008) Both Kathilankal et al (2008) and this study have a similar ecosystem and dominated plant species which could lead to similar pattern in the reduction of the CO2 flux exchange when flooding occurs.…”
Section: Influences Of Tide On Co2 Fluxes On Monthly Basismentioning
confidence: 99%
“…Few previous studies have shown that at a certain water table threshold, a reduction in CO2 exchange between salt marsh and atmosphere was observed (Forbrich and Giblin, 2015;Kathilankal et al, 2008;Moffett et al, 2010).…”
Section: Influences Of Tide On Co2 Fluxes On Monthly Basismentioning
confidence: 99%
See 1 more Smart Citation